The association between ECG criteria and Echo criteria for left ventricular hypertrophy in a general Chinese population. Issue 5 (26th July 2021) - Lv, Tingting; Yuan, Yifang; Yang, Jing; Wang, Guijin; Kong, Lingyun; Li, Huijuan; Li, Xingjie; Sun, Yingxian; Li, Xuewen; Zhang, Zheng; Cheng, Xiaoshu; Wu, Lirong; et al.
Abstract: Background: Several ECG criteria have been widely used for diagnosis of left ventricular hypertrophy (LVH) in clinical practice. However, their performance in a general Chinese population is limited. Methods and results: A multi‐stage, stratified cluster sampling across China was performed and 7415 representative Chinese adults aged 18–85 years were analyzed. ECG was collected by using GE MAC 5500 machine. The association between five ECG‐LVH criteria (i.e., Peguero–Lo Presti, Cornell, Cornell product, Sokolow–Lyon and Sokolow–Lyon product) and echocardiographic LVH (Echo‐LVH) was assessed by Pearson's correlation, diagnostic statistics like predictive values, and receiver operating characteristics (ROC) curve. We found that the prevalence of the Echo‐LVH was 11% while ECG‐LVH ranged from 3% to 27%. All ECG‐LVH criteria had high negative predictive value (NPV) (89%) and specificity (73–96%) but low positive predictive value (PPV) (12–24%) and sensitivity (4–29%). The newly Peguero–Lo Presti criteria had higher sensitivity (29%) but lower specificity (73%) and accuracy (68%) compared with other criteria. Cornell product had the best diagnostic performance (AUC: 0.59), as well as the highest specificity (96%) and accuracy (86%) but lowest sensitivity (4%). Among single‐lead components of ECG criteria, RaVL voltage and QRS duration performed relatively better than others. Hypertensive and older individuals had higher sensitivity but lower specificity and accuracy than their counterparts. Conclusion: ECG‐LVH criteria had high NPV to detect Echo‐LVH. Though with higher sensitivity, Peguero–Lo Presti criteria did not have better diagnostic performance to detect Echo‐LVH. RaVL and QRS duration had stronger association with Echo‐LVH among all single‐lead components.